Analisis Peran Teknologi Digital Sebagai Solusi Problematika Belajar Online yang Berkelanjutan - Nurul Kamilah; Husen Windayana (Jurnal Riset Madrasah Ibtidaiyah, 2022)
Since the COVID-19 pandemic struck Indonesia, there have been many changes that have affected various aspects of life, including education. The difficulties, among others, are the difficulty of getting materials, this makes the use of technology very much needed. This journal aims to review the important role of educational technology as a solution to learning problems during the pandemic, using a descriptive-analytical literature study method. The results of this review indicate that digital technology has an important role in the teaching and learning process during the current pandemic. Submission of material is also done using technology. In carrying out something, there are always obstacles and obstacles to be overcome, including those related to values, knowledge, attitudes, skills, and facilities and infrastructure used when learning online. Sufficient training and literacy can be a solution to face these challenges. Utilization of digital-based technology is considered effective and becomes a teacher's solution in carrying out online learning. The hope is that this digital technology can continue to be used as a sustainable medium.